Vitex negundo Inhibits Cyclooxygenase-2 Inflammatory Cytokine-mediated Inflammation on Carrageenaninduced Rat Hind Paw Edema - Pronobesh Chattopadhyay; Soilyadhar Hazarika; Sunil Dhiman; Aadesh Upadhyay; Anurag Pandey; Sanjeev Karmakar; Lokendra Singh (Pharmacognosy Research, 2012)
Background: Vitex negundo L. (Verbenaceae) is a hardy plant widely distributed in the Indian subcontinent and used for treatment of a wide spectrum of health disorders in traditional and folk medicine, some of which have been experimentally validated. In present study, we aimed to investigate the anti-inflammatory effects of V. negundo in carrageenan-induced paw edema in rats, and to investigate the probable mechanism of anti-inflammatory action. Materials and Methods: Paw edema was produced by injecting 1% solution of carrageenan, and the paw volume was measured before and after carrageenan injection up to 5 hr. V. negundo leaf oil was extracted using a Clevenger apparatus and administered by a trans-dermal route to Wistar rats and the percentage of inhibition of inflammation was observed using a Plethysmometer by comparing a compound aerosol-based formulation with 1 mg diclofinac diethylamine BP and 7 mg methyl salicylate IP/kg body weight served as a standard drug whereas paraffin oil served as the placebo group. After withdrawing of blood, serum was separated and cyclooxygenase (COX)-1 and COX-2 inhibitory activities were measured by the enzyme immuno assay (EIA) method by using a COX inhibitor screening assay kit. Results and Discussion: V. negundo leaf oil significantly (P < 0.05) reduced the carrageenan-induced paw edema as compared to the placebo group (paraffin oil) and 1 mg diclofinac diethylamine BP and 7 mg methyl salicylate IP showed the maximum inhibition of paw edema as compared to the V. negundo leaf oil treated group and the control group. Also in the present study V. negundo leaf oil showed significantly (P < 0.05) inhibits COX-1 pathways rather than COX-2 pathways as compared to the V. negundo leaf oil treated group. Conclusion: It is suggested that the V. negundo leaf oil is a potent anti-inflammatory agent and acts via inhibition of COX-2 without much interfering COX-1 pathways.
Keywords: Anti-inflammatory; Cyclooxygenase-2 inhibitors; Vitex negundo